Combined Endovascular and Microsurgical Management of Complex Cerebral Aneurysms - Choudhri, Omar; Mukerji, Nitin; Steinberg, MD, PhD, Gary K. (Frontiers in Neurology, 2013)
Cerebral aneurysms are associated with a 50% mortality rate after rupture and patients can suffer significant morbidity during subsequent treatment. Neurosurgical management of both ruptured and unruptured aneurysms has evolved over the years. The historical practice of using microsurgical clipping to treat aneurysms has benefitted in the last two decades from tremendous improvement in endovascular technology. Microsurgery and endovascular therapies are often viewed as competing treatments but it is important to recognize their individual limitations. Some aneurysms are considered complex, due to several factors such as aneurysm anatomy and a patient’s clinical condition. A complex aneurysm often cannot be completely excluded with a single approach and its successful treatment requires a combination of microsurgical and endovascular techniques. Planning such an approach relies on understanding aneurysm anatomy and thus should routinely include 3D angiographic imaging. In patients with ruptured aneurysms, endovascular coiling is a well-tolerated early treatment and residual aneurysms can be treated with intervals of definitive clipping. Microsurgical clipping also can be used to reconstruct the neck of a complex aneurysm, allowing successful placement of coils across a narrow neck. Endovascular techniques are assisted by balloons, which can be used in coiling and testing parent vessel occlusion before sacrifice. In some cases microsurgical bypasses can provide alternate flow for planned vessel sacrifice. We present current paradigms for combining endovascular and microsurgical approaches to treat complex aneurysms and share our experience in 67 such cases. A dual microsurgical–endovascular approach addresses the challenge of intracranial aneurysms. This combination can be performed safely and produces excellent rates of aneurysm obliteration. Hybrid angiographic operating-room suites can foster seamless and efficient complementary application of these two modalities.